Experiences with Osteoligamentoplasty According to Weiss for the Treatment of Scapholunate Dissociation. (4th July 2018) - Petersen, W.; Rothenberger, J.; Schaller, H. E.; Rahmanian-Schwarz, A.; Held, M.
ABSTRACT: Background : In post-traumatic, dynamic, or static scapholunate (SL) instability, an SL ligament reconstruction is advisable to avoid long-term complications. However, a sufficient primary reconstruction is best achieved in acute injuries. For chronic SL dissociation, there is still no satisfying standard surgical technique. In this context, we evaluated the clinical outcome of Weiss's osteoligamentoplasty as a treatment option. Methods : Over a three-year period, 16 patients with chronic and symptomatic SL dissociation Grade-II and III, without the signs of osteoarthrosis were, surgically treated using a bone-retinaculum-bone autograft from the distal radius. All patients underwent prior wrist arthroscopy. The clinical outcome was measured using the Mayo-Wrist, Krimmer, and DASH score. In addition, radiological measurements were also performed. Results : The postoperative clinical outcome successfully increased the Mayo-Wrist score: 32 to 64 points, Krimmer score: 30 to 53 points and DASH score: 41 to 30 points. The radiological follow-up demonstrated no evidence of an SL gap or significant loss of reposition in the SL angle in 13 of the 16 cases. Till date, two patients had to be revised to an arthrodesis. Conclusions : The autogenous osteoligamentary span from the distal radius improves a chronic SL dissociation and, therefore, presents a suitable option to anatomically reconstruct the SL ligament. It leads to a proper realignment of the carpus and could help to prevent arthritic changes of the wrist. Nevertheless, in patients with postoperative high occupational physical strain, the procedure should be performed with reservations. As long as there is no satisfying standard surgical treatment, Weiss's osteoligamentoplasty is a convincing technique.